Características morfológicas e produtivas da cultura da soja em função de diferentes arranjos espaciais de plantas - Müller, Alexandre Luis (2017)
The aim of the present work was to evaluate the morphological and productive characteristics of the soybean crop submitted to different spacings between rows and plant populations. The experiment was conducted at the Experimental Farm of PUCPR - Campus Toledo, using cultivar NA5909RG. The experimental design was a randomized blocks design, in a 2 x 6 x 5 factorial scheme, with cultivation years (2013/2014 and 2014/2015), spacing between rows (15, 30, 45, 60, 75 and 90 cm) and plant populations (10, 20, 30, 40 and 50 plants m-2) with four replications. At the grain filling stage (R5), the following variables were evaluated: percentage of soil cover; plant height; stem diameter; number of nodes; leaf area index. At the end of the crop cycle, the following variables were evaluated: number of surviving plants, number of pods per plant, number of grains per pod, mass of one thousand grains and yield of grains. There was interaction between plant population and row spacing for soil cover variable, plant height, number of end plants and number of pods per plant, for the other variables no interation occurred, only the isolated effect of each factor. In the lower plant populations, the decrease in height, total dry mass and leaf area index, and increase in diameter, number of nodes, number of pods, grains per pod and consequently of productivity. For the smaller spacings decrease of the dry mass total, index of leaf area and the mass of a thousand grains. Therefore, the increase of the population of plants reduced the number of plants at the end of the cycle and the smaller plant populations increase grain yield, regardless of the plant spacing adopted.